2019
DOI: 10.1097/md.0000000000014369
|View full text |Cite
|
Sign up to set email alerts
|

Pathomorphological features of metastatic lymph nodes as predictors of postoperative prognosis in pancreatic cancer

Abstract: To investigate the pathological features of metastatic lymph nodes (LN) in pancreatic ductal adenocarcinoma (PDAC) and to determine factors with prognostic implications. Metastatic LN status is a proven significant factor for predicting postoperative prognosis in pancreatic cancer patients. However, the effective prognostic criteria regarding metastatic LNs for such disease remain unknown. We retrospectively reviewed 98 patients with R0/1 resection for PDAC. All metastatic LNs were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…Lymph node metastases is considered a grave prognostic sign in PDAC. Tumor size and lymph node involvement are significantly correlated with OS [2,20,21]. Previous study showed that tumor size was found to be an important predictor of lymph node status and predicted odds of positive nodes tend to increase with increasing tumor size [22].…”
Section: Discussionmentioning
confidence: 95%
“…Lymph node metastases is considered a grave prognostic sign in PDAC. Tumor size and lymph node involvement are significantly correlated with OS [2,20,21]. Previous study showed that tumor size was found to be an important predictor of lymph node status and predicted odds of positive nodes tend to increase with increasing tumor size [22].…”
Section: Discussionmentioning
confidence: 95%
“…27 In a Japanese single institution study of 98 PDAC patients, PTLNI was found in 27 patients (27.6%). 28 They reported that there was no statistically significant difference in survival outcomes between patients with PTLNI and patients without LN metastasis. The current study demonstrated that PTLNI group had similar survival outcomes compared to N0 patients in terms of median disease-free survival duration and rate.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have investigated the effect of PTLN invasion on the prognostic outcome. [24][25][26][27][28] The first study in the literature on PTLN was published in 2010 by Massachusetts General Hospital group. 24 They reviewed 517 patients who underwent pancreatic resection for PDAC and found direct invasion in at least 20% of patients with one or two LN metastases.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is not surprising that treatment response (CR/nCR) in the primary tumor is uncommon, regardless of the type of neoadjuvant therapy delivered. However, PC metastases lose the characteristic stromal component and may even be difficult to distinguish from liver, lung, or ovarian neoplasms (41,42). In a well-vascularized environment which is depleted of the immunosuppressive stroma, PC metastases may become susceptible to both chemotherapeutic agents as well as chemoradiation.…”
Section: Discussionmentioning
confidence: 99%